1986
DOI: 10.3109/03008208609167140
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Culture of Human Chondrocytes From Adult Subjectsm

Abstract: An agarose gel matrix was utilized to grow chondrocytes from human donors of various ages in cell culture. The chondrocytes produced the pericellular matrix characteristic for such cells and synthesized collagen type II as well as glyco-saminoglycans. The latter exhibit the typical distribution pattern of the respective articular cartilage matrix. The electron-microscopic appearance of the cultured chondrocytes closely resembles that of chondrocytes in sections of the original cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…This result confirms the findings of Delbruck et al (1986). The proteoglycans synthesized in vitro were identical to those of the native cartilage, with respect to molecular weight and length of glycosaminoglycan chains.…”
Section: Esupporting
confidence: 81%
See 1 more Smart Citation
“…This result confirms the findings of Delbruck et al (1986). The proteoglycans synthesized in vitro were identical to those of the native cartilage, with respect to molecular weight and length of glycosaminoglycan chains.…”
Section: Esupporting
confidence: 81%
“…drocyte culture methods were developed primarily using animal tissues, as in studies of limb development (Solursh et al, 1986), and have now been applied to human cells. Delbruck et al (1986) showed that human articular cells in agarose culture produced type I1 collagen. Synthesis of type II collagen and cartilage-specific proteoglycans by chondrocytes has been shown by Bassleer et al (1986).…”
Section: Discussionmentioning
confidence: 99%
“…For organ cultures pieces of cartilage of equal size were embedded in 0.75°/0 low-gellingtemperature agarose and cultured in Opti-MEM 1 supplemented with 10070 FCS, 10/0 Ultroser G, 1 #g/ml insulin and 50/zg/ml ascorbic acid. For agarose cultures chondrocytes were isolated by collagenase treatment essentially as described [20,21]. Culture medium was the same as described above.…”
Section: In Vitro Culture Of Human Chondrocytesmentioning
confidence: 99%
“…Hence, the genes that are strong candidates for sites of mutations that cause chondrodysplasias are not expressed in vitro. However, modu lated epiphyseal chondrocytes from many species reexpress the phenotype of the typi cal chondrocyte if cultured in or on agarose gels [36][37][38][39]. Furthermore, in the chick at least, such '^differentiated' chondrocytes subsequently express the phenotype of the hypertrophic chondrocyte if maintained in agarose culture [37,38].…”
Section: In Vitro Studiesmentioning
confidence: 99%